Prevention of relapse after allogeneic stem cell transplantation in acute myeloid leukemia: Updates and challenges. Issue 2 (28th November 2019) - Thekkudan, Shinto F.; de Lima, Marcos; Metheny, Leland
Abstract: Allogeneic hematopoietic stem cell transplantation (allo‐HSCT) is a potentially curative treatment for acute myeloid leukemia (AML). Reduced intensity regimens, alternative graft sources, advances in HLA‐matching, improved supportive care, and tailored graft versus host disease (GVHD) prophylaxis have led to a wider application of allo‐HSCT to eligible patients. Unfortunately, 30‐40% of patients with AML will relapse after transplant and this is the major cause of treatment failure. Careful consideration should be paid in choosing the type of graft, graft source, and conditioning regimen to minimize the risk of disease recurrence. In addition, maintenance therapy following allo‐HSCT is a potential method to keep the disease in remission, especially in those with high‐risk disease characteristics. Pharmacological targeted agents with low side effect profile such as tyrosine kinase inhibitors, hypomethylating agents (HMAs), HDAC inhibitors, antibody drug conjugates (ADCs), isocitrate dehydrogenase inhibitors, and hedgehog inhibitors may prevent relapse in posttransplant setting and are under investigation. Immunological therapies including donor lymphocyte infusions (DLIs), natural killer (NK) cell therapy, peptide vaccine targeting tumor antigens, and adoptive T‐cell therapies all hold promises in this area as well. As targeted agents and immunotherapies continue to be developed, patients at high risk of recurrence may benefit from prophylactic maintenance therapy. Here we review the current landscape in this rapidly evolving clinical setting.